Bridging Cultures in the Digital Era: Pedagogical Strategies for a Culturally Responsive Classroom - Mahbub Zuhri; Naser Ali Abdulghani; Muhammad Sularno; Mujhid Budi Luhur; RM. Imam Abdillah (Tunjuk Ajar: Journal of Education and Culture, 2025)
This qualitative case study investigates culturally responsive digital pedagogical practices in a multicultural Indonesian high school. Through semi-structured interviews, participatory observation, and document analysis involving three teachers and twelve students, the study reveals three core patterns of culture-technology integration: (1) contextual learning designs that incorporate local wisdom, (2) dialogic and egalitarian digital interactions, and (3) affirmation of cultural identity in digital learning spaces. The findings underscore that the success of digital pedagogy depends not on technological sophistication, but on the teacher’s role as a cultural mediator and facilitator of reflective dialogue. This study contributes to the global discourse on culturally responsive digital pedagogy by offering empirical evidence from the underrepresented Indonesian context and proposing an initial conceptual model relevant to Southeast Asian socio-cultural settings. The model emphasizes contextual design, reflective dialogue, and identity affirmation as foundational pillars. Practical implications highlight the need for teacher professional development programs focused on digital-cultural competencies and equitable infrastructure policies to support inclusive digital transformation. The study also aligns with Indonesia’s Merdeka Curriculum and national digitalization initiatives, advocating for pedagogy that harmonizes technology with local cultural values.